Lamiaceae in Parque Estadual do Juquery (PEJY), Southeast Brazil - Conegiro, Thaís Teixeira; Bruniera, Carla Poleselli (Phytotaxa, 2025)
This study consisted of a floristic survey of Lamiaceae in Parque Estadual do Juquery (PEJY), a Conservation Unit located in São Paulo’s metropolitan area (in Franco da Rocha and Caieiras cities) which is considered the biggest Cerrado refuge of the state. It possesses a high biodiversity, however, is constantly threatened due to the indiscriminate use of fire by men. To access the diversity of Lamiaceae in PEJY we analyzed herbaria collections and made field expeditions between 2022 and 2023. We recorded 17 Lamiaceae species (15 native to Brazil) occurring in PEJY, arranged in 12 genera: Aegiphila (1 spp.), Cantinoa (2 spp.), Eriope (1 spp.), Hyptis (3 spp.), Leonurus (1 spp.), Leucas (1 spp.), Medusantha (1 spp.), Mesosphaerum (2 spp.), Ocimum (1 spp.), Rhabdocaulon (1 spp.), Salvia (2 spp.), and Vitex (1 spp.). Here we provide comprehensive treatments for all native species recorded; notably, for Hyptis marrubioides, Ocimum carnosum, and Salvia minarum, these are the first detailed descriptions since their original descriptions. Finally, this work brings seven new occurrences for the area, highlighting the importance of floristic studies for specific groups or families, especially the ones with a high diversity of herbs and shrubs.